Chondroitin-4-sulfation negatively regulates axonal guidance and growth - Wang, Hang (2008)
Glycosaminoglycan (GAG) side chains endow extracellular matrix proteoglycans with diversity and complexity based upon the length, composition, and charge distribution of the polysaccharide chain. Using cultured primary neurons, we show that specific sulfation in the GAG chains of chondroitin sulfate (CS) mediates neuronal guidance cues and axonal growth inhibition. Chondroitin-4-sulfate (CS-A), but not chondroitin-6-sulfate (CS-C), exhibits a strong negative guidance cue to mouse cerebellar granule neurons. Enzymatic and gene-based manipulations of 4-sulfation in the GAG side chains alter their ability to direct growing axons. Furthermore, 4-sulfated CS GAG chains are rapidly and significantly increased in regions that do not support axonal regeneration proximal to spinal cord lesions in mice. Thus, our findings provide the evidence showing that specific sulfation along the carbohydrate backbone carries instructions to regulate neuronal function.